Determination of exercise attitudes of women of reproductive age in pregnancy - Feyza Aktaş Reyhan (Elsevier, 2024)
Objective: This study was conducted to evaluate the exercise attitudes of women of reproductive age during pregnancy. Method: The descriptive study was conducted with 326 women who applied to the gynecology outpatient clinics of a state hospital between September and November 2023. Data were collected with the ''Personal Information Form'' and ''Exercise Attitudes in Pregnant Women Scale''. Statistical analyses were analyzed at p < .05 significance level with the independent samples t test method. Results: Most of the participants (85.6%) stated that they did not know the benefits of exercise during pregnancy and did not exercise during pregnancy (89.6%). The mean exercise attitude scale score of the participants was 135.42 ± 25.90. A significant difference was found between the participants' education level, exercising outside pregnancy, attending a pregnancy school, knowing the benefits of exercise during pregnancy and exercising during pregnancy and all sub-dimension scores (p < .05). Conclusion: In the study, it was observed that the participants had positive attitudes towards exercise during pregnancy, although their knowledge and behaviors were insufficient. Women's attitudes towards exercise should be determined by health professionals and women's positive attitudes, knowledge and behaviors should be improved by organizing trainings and exercise programs starting from pre-pregnancy.